Relationship Between Technology Literacy and Communication Skills with Environmental Literacy of Class X Students of SMAN 2 Malang - Zakiyatus Sarifah; Fatchur Rohman; Mimien Henie Irawati Al-Muhdhar; Ruchimah Achmad; Laily Asfaniy (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
The aim of this study is to determine the relationship between technology literacy and communication skills in environmental literacy of class X SMAN 2 Malang. The methods using survey research with a correlational design to determine the relationship. Research subjects selected using simple random sampling. The subjects are 34 class X students of SMAN 2 Malang in social sciences and language majors. The research instruments are questionnaires on technology literacy and communication skills, and environmental literacy questionnaires and tests. Data analysis includes prerequisite, correlation and regression tests. The results showed that the values of technology literacy, communication skills, and environmental literacy are classified in the high category. The correlation between technology literacy and environmental literacy is -0.007 classified as very low category, the correlation between communication skills and environmental literacy is -0.207 classified as very low category, the correlation between technology literacy and communication skills is -0.903 classified as very strong category, and the correlation between technology literacy and communication skills together with environmental literacy is 0.048 classified as very low category.